A study on the efficiency of customer service at DAHE Industries Malaysia (DIM) Sdn Bhd / Normayanti Omar - Omar, Normayanti (Faculty of Business and Management, 2001)
DAHE Industries Malaysia Sdn Bhd main business is mainly on the manufacturing and supply of high quality Steel Gratings. These Gratings are catering for the Oil and Gas sector and other users looking for high quality products. This research, which studies the efficiency of customer service at DIM and could give some idea to DIM regarding its performance to customers.